Micro-turbine design point definition using optimization techniques - Diogo Ferraz Cavalca (2012)
During a gas turbine development phase an important engineer task is to find the appropriate engine design point that meet all required specifications. This task can be very arduous because all possible operating points in the gas turbine operational envelope need to be analyzed, for the sake of verification of whether or not the established performance might be achieved. In order to support engineers to best define the engine design point that meet required performance a methodology was developed in this work. To accomplish that a computer program was written in Matlab@. In this program was incorporated the thermoeconomic and thermodynamic optimization using genetic algorithm with single and multi-objective. The thermodynamic calculation process was done based in enthalpy and entropy function and then validated using a commercial program. In this work the study was done for a recuperated micro-turbine. Cycle efficiency, total cost and specific work were chosen as objective functions, while pressure ratio, compressor and turbine polytropic efficiencies, turbine inlet temperature and heat exchange effectiveness were chosen as decision variables. Total cost considers the fixed cost (equipment, installation, etc.) and variable cost (fuel, environmental and O&M). For emissions calculations were taken into account the NOx, CO and UHC. An economic analysis was done showing the costs behavior for diffierent optimized design points. The optimization process was made for single-objective, two-objective and three-objective. After, the results were compared each other showing the possible design points.